A Review of Sustainable Consumption (2000 to 2020): What We Know and What We Need to Know. Issue 5 (19th October 2020) - Quoquab, Farzana; Mohammad, Jihad
Abstract: Owing to environmental pollution and care for natural resources, the notion of sustainable consumption has gained significant research attention. However, studies on sustainable consumption are still in their infancy and need further development. With a view to providing a broader perspective on this issue, this study systematically reviewed the relevant literature published between 2000 and 2020 and synthesized the existing knowledge in order to understand what we know thus far and what we need to know to understand the wider dimensions of the phenomenon. More specifically, this study has answered eight major questions: How has this concept emerged? How can the notion of sustainable consumption be conceptualized in a holistic manner? What are the major facets of sustainable consumption? What theories are being considered in relation to this phenomenon? What methodologies are being utilized? What are the predictors of sustainable consumption? What is the outcome of sustainable consumption? What mediators/moderators are being considered in relation to this concept? This study calls for more research to be conducted to fill the gaps in the existing literature.